3(y-9)-2y=6

Simple and best practice solution for 3(y-9)-2y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-9)-2y=6 equation:


Simplifying
3(y + -9) + -2y = 6

Reorder the terms:
3(-9 + y) + -2y = 6
(-9 * 3 + y * 3) + -2y = 6
(-27 + 3y) + -2y = 6

Combine like terms: 3y + -2y = 1y
-27 + 1y = 6

Solving
-27 + 1y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 1y = 6 + 27

Combine like terms: -27 + 27 = 0
0 + 1y = 6 + 27
1y = 6 + 27

Combine like terms: 6 + 27 = 33
1y = 33

Divide each side by '1'.
y = 33

Simplifying
y = 33

See similar equations:

| g+8=-24 | | 144=x+23 | | 6(z-2)-5z=12 | | 12-3x+7x=-2(-5+6) | | 4-4(x-1)-(3x+4)=2(x-6) | | 4.1+3.3+4.37= | | (40)2/5= | | 8h-7h+9=1 | | 9z/3= | | 20x+25y=1115 | | (x+8)(x-5)=9 | | 2(x-3)+3(x-4)=6(x+3) | | 9(m-3)-4(4m-7)= | | 1.3=y+5.3 | | 6g^12= | | x+x-40=280 | | 6y+5c+w=22 | | 5y-1=4-7y | | 5x-4+18-8x=3x-16 | | s=2g+2w | | J-41=-25 | | 2x/3-1/4=1/3 | | 72--=6r | | l-5x+12lx=5 | | -3(5c-d)= | | x+14,223=119425 | | 64+116=180 | | 5k-5k+40=-40 | | 4+4(4x-6)=7-3(2x+1) | | 18=2x+9y | | x-42=18 | | 11(b-8)-5(9b+7)= |

Equations solver categories